PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA SD MELALUI METODE CERITA BERGAMBAR DALAM PEMBELAJARAN BAHASA INDONESIA - Sheza Nazwa Aulia; Siti Rohmah; Desty Endra Wati Subroto (CV. Denasya Smart Publisher, 2025)
The ability to read comprehension is one aspect of the skills that elementary school students need to have. However, many students still experience difficulties in understanding the content of the text they read. This article examines the use of picture story method as a strategy to improve students reading comprehension skills. This method integritas visual element with narrative text,thereby helping students more easily understand the content of the reading. Apart from improving understanding of the illustrated stories also play a role in increasing students interest and motivation to learn. This article advocates the wider application of the picture story method in Indonesia language learning in elementary schools